DETERMINANT INTENTION TO USE MERCHANT QRIS UMKM MICRO BANK BPD BALI - Kemala, Gusti Ayu Diah Chandra; Darma, Gede Sri (UNIVERSITAS PAKUAN, 2017)
The use of technology (QIRS) as a non-cash payment tool has been utilized by Micro MSMEs. Usefulness, Ease of Use, and Risk will influence the user's intention to use technology. This research aims to analyze the influence of perceived usefulness, perceived ease of use, and perceived risk on intentions to use QRIS Bank BPD Bali merchants which is moderated by user experience. This research took quantitative data using the MRA method with a total of 397 Micro MSMEs as respondents. The research results show that the variable perceived usefulness has no influence on the intention to use QRIS BPD Bali merchants, while perceived ease of use and perceived risk influence the intention to use QRIS BPD Bali merchants. Apart from that, user experience is not able to moderate the influence of perceived usefulness on the intention to use QRIS BPD Bali merchants. However, it is able to strengthen perceived ease of use and perceived risk which influence the intention to use QRIS BPD Bali merchants.